A diaphragm binder composition, diaphragm binder powder, diaphragm and battery
By using a separator adhesive composition composed of polymer particles A and B of a specific range, the problem of difficult bonding of lithium-ion battery separators at room temperature is solved, effective bonding between the separator and the electrode sheet is achieved, and the charging and discharging efficiency and safety of the battery are improved.
Patent Information
- Application Number
- CN202411866445.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
During the preparation process, existing lithium-ion battery separators have problems such as high cost, complex production, unfriendly environment and difficulty in achieving effective bonding at room temperature, which affects the charging and discharging efficiency and safety of the battery.
A separator adhesive composition is adopted, which includes polymer particles A with a glass transition temperature Tg of -10°C or less and an average particle diameter D50 of 500 nm or more, and polymer particles B with a Tg of 60°C or more and D50 of 300 nm or less. The separator adhesive powder is prepared by spray drying, and the effective bond between the separator and the electrode sheet is achieved by applying pressure at room temperature.
It can avoid self-adhesion of the diaphragm without applying pressure at room temperature, improve the processing performance of the battery, and effectively bond between the diaphragm and the electrode sheet after applying pressure at room temperature, improving the charging and discharging efficiency and safety of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a diaphragm binder composition, a diaphragm binder powder, a diaphragm and a battery. Background Art
[0002] With the development of social economy and the advancement of science and technology, people's demand for energy continues to grow, and the consumption of traditional fossil energy not only causes the problem of resource depletion, but also triggers serious environmental problems.
[0003] Among many new energy technologies, lithium-ion batteries have become one of the most eye-catching research objects due to their advantages such as high energy density, long life and no memory effect.
[0004] Lithium-ion battery is a rechargeable battery (secondary battery) whose working principle is based on the movement of lithium ions between positive and negative electrodes.
[0005] A typical lithium-ion battery structure includes a positive electrode material, a negative electrode material, an electrolyte, and a separator between the positive and negative electrodes.
[0006] Among them, the separator is not only a key component that physically separates the positive and negative electrodes, but also an important medium to ensure that lithium ions can pass freely for charging and discharging reactions.
[0007] The quality of the separator directly affects the safety, cycle life and charge and discharge efficiency of the battery.
[0008] The main function of the separator is to physically prevent the positive and negative electrodes from directly contacting each other and causing a short circuit, while allowing lithium ions to pass smoothly.
[0009] In addition, the separator must have good chemical stability, mechanical strength and thermal stability to adapt to the complex electrochemical environment inside the battery.
[0010] The lithium-ion battery separators widely used in the current market are mostly porous membranes made of polyolefin materials, such as polyvinylidene fluoride (PVDF). Although these materials have good thermal stability and chemical inertness, they have problems such as high cost, complex production process, and environmental unfriendliness.
[0011] In addition, organic solvents are required in the preparation process of fluorine-containing polymer coatings, which not only increases production costs, but also may cause environmental pollution and safety hazards. More importantly, traditional fluorine-containing coatings are difficult to achieve effective bonding effects at room temperature. Although the commonly used hot pressing process can achieve good bonding effects, it also brings problems such as micro-deformation of the diaphragm and pore blockage, which affects the migration path of lithium ions, reduces the charging and discharging efficiency of the battery, and even causes safety hazards.
[0012] Therefore, it is of great significance to develop a diaphragm adhesive that can achieve good bonding between the diaphragm and the electrode at room temperature. Summary of the invention
[0013] In order to solve the above technical problems, the present invention provides a diaphragm adhesive composition, a diaphragm adhesive powder, a diaphragm and a battery that can achieve good bonding between a diaphragm and a pole piece at room temperature.
[0014] In a first aspect, a diaphragm adhesive composition comprises polymer particles A and polymer particles B, wherein the glass transition temperature Tg of the polymer particles A is below -10°C, the glass transition temperature Tg of the polymer particles B is above 60°C, the average particle size D50 of the polymer particles A is above 500nm, and the average particle size D50 of the polymer particles B is below 300nm.
[0015] In the present invention, when the diaphragm adhesive composition contains polymer particles A having a glass transition temperature Tg of less than -10°C and an average particle size D50 of more than 500nm, and polymer particles B having a glass transition temperature Tg of more than 60°C and an average particle size D50 of less than 300nm, after the powder formed by the diaphragm adhesive composition is used to make a diaphragm slurry and coated on the surface of the base film, polymer particles B are distributed on the surface of the polymer particles A with larger particle size. In the non-pressurized diaphragm preparation and winding process, the diaphragm will not self-stick, which greatly improves the processing performance.
[0016] At the same time, when bonding the diaphragm and the electrode to prepare the battery cell, effective bonding between the diaphragm and the electrode can be achieved by simply applying a certain amount of pressure at room temperature.
[0017] Furthermore, the use of polymer particles A and polymer particles B having a glass transition temperature and an average particle size within the above-mentioned specific range can effectively prevent the coating layer from clogging the micropores of the base film, thereby preventing the decrease in the air permeability of the prepared separator.
[0018] Preferably, in the diaphragm adhesive composition, the mass ratio of the polymer particles A to the polymer particles B is (5-9): (1-5).
[0019] In the present invention, when the mass ratio of polymer particles A to polymer particles B is within the above range, it is more conducive to ensuring that self-adhesion does not occur during diaphragm processing, and when preparing the battery cell, effective bonding between the diaphragm and the electrode is achieved by applying pressure at room temperature.
[0020] Preferably, the mass ratio of the polymer particles A to the polymer particles B is (6-8):(2-4).
[0021] Preferably, the ratio of the average particle size of the polymer particles A to that of the polymer particles B is (5-15):3.
[0022] In the present invention, the ratio of the average particle size of polymer particles A to that of polymer particles B is within the above-mentioned range, which is very beneficial to further achieving the purpose of the present invention, that is, it is more conducive to achieving effective bonding between the diaphragm and the electrode under pressure at room temperature, and can effectively avoid self-adhesion during diaphragm processing; and it is beneficial to further suppress the decline in the air permeability of the diaphragm.
[0023] In a further preferred embodiment, the ratio of the average particle size of the polymer particles A to that of the polymer particles B is (8-12):3.
[0024] Preferably, the glass transition temperature Tg of the polymer particles A is -70 to -10°C, and the average particle size D50 of the polymer particles A is 500 to 1500 nm.
[0025] The glass transition temperature Tg of the polymer particles B is 60-150° C., and the average particle size D50 of the polymer particles B is 100-300 nm.
[0026] Specifically, the glass transition temperature Tg of the polymer particles A can be -10°C, -15°C, -20°C, -25°C, -30°C, -35°C, -40°C, -45°C, -50°C, -55°C, -60°C, -65°C, or -70°C.
[0027] The average particle size D50 of the polymer particles A can be 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, 1050 nm, 1100 nm, 1150 nm, 1200 nm, 1250 nm, 1300 nm, 1350 nm, 1400 nm, 1450 nm, or 1500 nm.
[0028] The glass transition temperature Tg of polymer particles B may be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, or 150°C.
[0029] The average particle size D50 of the polymer particles B may be 100 nm, 150 nm, 200 nm, 250 nm, or 300 nm.
[0030] Preferably, polymer particles B are distributed on the surface of the polymer particles A, and the surface of the polymer particles A is at least partially covered by the polymer particles B.
[0031] In the present invention, when the aforementioned polymer particles A and polymer particles B have the above-mentioned distribution state, during the processing of the diaphragm, the polymer particles B having the aforementioned glass transition temperature and particle size can provide effective structural support, and the polymer particles B will encapsulate the polymer particles A which mainly provide the bonding effect, and the polymer particles exposed to the outside will not provide bonding force at room temperature and will not cause self-adhesion; and when preparing the battery cell, the polymer particles A having the aforementioned glass transition temperature and particle size are relatively soft and provide the main bonding force. After pressure is applied, the polymer particles A are exposed, contact with the base film and the electrode of the diaphragm, and achieve bonding.
[0032] At the same time, since polymer particles B are mainly distributed on the surface of polymer particles A rather than in a discrete distribution state, it is very beneficial to maintain the porosity of the coating layer containing the diaphragm binder and avoid clogging the micropores of the diaphragm base membrane, thereby inhibiting the decrease in the air permeability of the diaphragm.
[0033] In the present invention, the specific material of the polymer particles A and B is not particularly limited, and various polymer materials commonly used in the prior art can be used.
[0034] In order to better achieve the purpose of the present invention, preferably, the polymer particles A include vinyl structural units, acrylic ester structural units and functional structural units;
[0035] The vinyl structural unit is selected from one or more of a styrene structural unit, an acrylonitrile structural unit, a methylstyrene structural unit, an ethylstyrene structural unit, an acrylamide structural unit, and a methacrylamide structural unit. In the present invention, the vinyl structural unit is preferably a styrene structural unit and / or an acrylamide structural unit.
[0036] In the present invention, the styrene structural unit can form a polymer having good transparency, rigidity and chemical resistance.
[0037] The presence of styrene structural units can improve the hardness and modulus of the final material, and also enhance the gloss and surface smoothness of the material. The acrylamide structural unit has good water solubility and hydrophilicity. Its presence can make the polymer have better water absorption and wettability, which can promote the absorption and transmission of electrolyte. Both styrene and acrylamide have good reactivity and are easy to carry out emulsion polymerization, which not only simplifies the production process but also improves production efficiency.
[0038] The acrylic acid ester structural unit is selected from one or more of a methyl acrylate structural unit, an ethyl acrylate structural unit, a n-propyl acrylate structural unit, an isopropyl acrylate structural unit, a n-butyl acrylate structural unit, an isobutyl acrylate structural unit, a tert-butyl acrylate structural unit, a n-pentyl acrylate structural unit, a n-hexyl acrylate structural unit, an isooctyl acrylate structural unit, a methyl methacrylate structural unit, an ethyl methacrylate structural unit, a propyl methacrylate structural unit, an isopropyl methacrylate structural unit, a n-butyl methacrylate structural unit, an isobutyl methacrylate structural unit, a tert-butyl methacrylate structural unit, a n-pentyl methacrylate structural unit, a n-hexyl methacrylate structural unit, a n-octyl methacrylate structural unit, an isooctyl methacrylate structural unit, a lauryl methacrylate structural unit, and a cyclohexyl methacrylate structural unit;
[0039] The functional structural unit is selected from one or more of acrylic acid structural unit, methacrylic acid structural unit, vinyl acrylic acid structural unit, β-acryloxypropionic acid structural unit, hydroxyacrylic acid, maleic acid structural unit, itaconic acid structural unit, monobutyl itaconate structural unit, hydroxyethyl acrylate structural unit, hydroxypropyl acrylate structural unit, hydroxyethyl methacrylate structural unit, hydroxypropyl methacrylate structural unit, hydroxymethyl acrylamide structural unit, hydroxyethyl acryloyl urea structural unit, caprolactone acrylate structural unit, polyethylene glycol monomethacrylate structural unit, and phenyl glycidyl ether acrylate structural unit.
[0040] Preferably, in the polymer particles A, the mass ratio of the vinyl structural unit, the acrylate structural unit and the functional structural unit is (0-35): (60-95): (1-5).
[0041] Preferably, the polymer particles B include a main structural unit and a cross-linking structural unit;
[0042] The main structural unit is selected from one or more of a methyl acrylate structural unit, an ethyl acrylate structural unit, a n-propyl acrylate structural unit, an isopropyl acrylate structural unit, a n-butyl acrylate structural unit, an isobutyl acrylate structural unit, a tert-butyl acrylate structural unit, a n-pentyl acrylate structural unit, a n-hexyl acrylate structural unit, an isooctyl acrylate structural unit, a styrene structural unit, a methyl styrene structural unit, an acrylamide structural unit, a methacrylamide structural unit, a methyl methacrylate structural unit, a glycerol formal methacrylate structural unit, an isobornyl acrylate structural unit, an isobornyl methacrylate structural unit, an acrylic acid structural unit, a methacrylic acid structural unit, and an itaconic acid structural unit;
[0043] The cross-linking structural unit is selected from one or more of diol diacrylate structural units, bisphenol A diacrylate structural units, azacycloalkane diacrylate structural units, divinyl aromatic hydrocarbon structural units, diol dimethacrylate structural units, bisphenol A dimethacrylate structural units, trimethylolpropane triacrylate structural units, trimethylolpropane trimethacrylate structural units, and pentaerythritol tetraacrylate structural units.
[0044] Preferably, in the polymer particles B, the mass ratio of the main structural unit to the cross-linking structural unit is 100:(2-10).
[0045] As is well known to those skilled in the art, in the aforementioned polymer particles A and B, the "certain" structural unit refers to a structural unit existing in a "certain monomer" after a corresponding polymer is obtained by polymerization of the "certain monomer". For example, an acrylate structural unit refers to a structural unit derived from an acrylate monomer in the polymer particles A obtained after the acrylate monomer participates in the polymerization.
[0046] Likewise, in the present invention, the mass ratio of various structural units in the aforementioned polymer particles is based on the mass ratio of various monomers involved in the polymerization to obtain the polymer particles.
[0047] The aforementioned polymer particles A and B can be prepared by conventional methods in the field of chemical synthesis, which will not be described in detail in the present invention.
[0048] When the materials of polymer particles A and B respectively meet the above conditions, it is more beneficial to further improve the adhesion and avoid self-adhesion.
[0049] The above-mentioned diaphragm adhesive composition provided by the present invention is usually in the form of an emulsion, and the polymer particles A and B are distributed in the solvent in the form of suspended particles.
[0050] Generally, there is no limit to the content of the solvent, and the relative content of the polymer particles A and B and the solvent can be adjusted accordingly according to the actual solid content requirements.
[0051] Usually, the above solvent is deionized water.
[0052] In a second aspect, the present invention provides a diaphragm binder powder, which is a secondary particle formed by the diaphragm binder composition as described above, and the secondary particle includes polymer particles A and polymer particles B distributed on the surface of polymer particles A, and the surface of polymer particles A is at least partially covered by polymer particles B.
[0053] The above-mentioned diaphragm adhesive powder can be prepared by spray drying the diaphragm adhesive composition provided by the present invention. For example, a spray dryer is used to spray dry the above-mentioned diaphragm adhesive composition. The specific conditions of spray drying can be those known in the prior art, for example, an inlet air temperature of above 180°C and an outlet air temperature of 80~100°C.
[0054] The diaphragm binder composition is used to obtain a diaphragm binder powder having the above-mentioned structure by spray drying.
[0055] In a third aspect, the present invention provides a diaphragm, wherein the diaphragm comprises the diaphragm binder powder as described above.
[0056] The method of preparing a diaphragm using the aforementioned diaphragm adhesive composition or diaphragm adhesive powder is well known in the prior art. For example, the diaphragm adhesive powder, auxiliary adhesive, additive, and solvent are mixed in a mass ratio of (10-15): (1-3): (0.5-2): (80-90), and a coating slurry is obtained after dispersion. The coating slurry is then applied to the surface of the diaphragm substrate and rolled up after drying.
[0057] Since the membrane adhesive composition or membrane adhesive powder provided by the present invention will hardly adhere at room temperature and without pressure, an auxiliary adhesive needs to be added when preparing the membrane to achieve stable adhesion of the coating slurry on the surface of the membrane base film.
[0058] In the present invention, the auxiliary adhesive can be selected from one or more of the commonly used acrylic adhesives, SBR (styrene butadiene rubber) adhesives, PAA (polyacrylic acid) adhesives, and PAN (polyacrylonitrile) adhesives in the art. For example, SWA610 produced by Shenzhen Haodian Technology Co., Ltd. can be used.
[0059] The aforementioned auxiliary agent can be any commonly used one in the art, for example, can be selected from surfactants and defoamers. Specifically, the auxiliary agent can be one or more of fluorocarbon surfactants, polysiloxane defoamers, and white mineral oil.
[0060] Deionized water can be used as the solvent.
[0061] In a fourth aspect, the present invention provides a battery, comprising the separator as described above.
[0062] The method for preparing a battery using the diaphragm provided by the present invention may be a conventional method in the prior art, which will not be described in detail in the present invention. DETAILED DESCRIPTION
[0063] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0064] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the protection scope of the present invention.
[0065] Example 1
[0066] The present embodiment provides a method for preparing a diaphragm binder powder, comprising the following steps: compounding polymer particles A and polymer particles B at a mass ratio of 5:1 and obtaining the powder by spray drying (inlet air temperature 180° C., outlet air temperature 90° C.).
[0067] The preparation method of polymer particles A comprises: adding 80 parts of water and 1 part of sodium bicarbonate into a reaction kettle, introducing nitrogen for 30 minutes, heating the sealed container to 75°C for reaction for 15 minutes, adding 1 part of ammonium persulfate, 0.2 parts of sodium dodecylbenzene sulfonate, 80 parts of water, 50 parts of butyl acrylate, 20 parts of isooctyl acrylate, 38 parts of styrene, and 3 parts of methacrylic acid, reacting at 75°C for 2 hours, keeping the temperature for 1 hour, heating to 85°C for reaction for 1 hour, keeping the temperature for 2 hours, cooling to 40°C, and terminating the reaction to obtain an emulsion of polymer particles A, wherein the glass transition temperature of polymer particles A is -15°C, and the particle size D of polymer particles A is 551 nm;
[0068] The preparation method of polymer particles B comprises the following steps: adding 80 parts of water, 1 part of sodium bicarbonate and 0.5 parts of emulsifier into a reaction kettle, introducing nitrogen for 30 minutes, heating the sealed container to 85°C and reacting for 15 minutes, adding 1 part of ammonium persulfate, 1 part of sodium dodecylbenzene sulfonate, 80 parts of water, 85 parts of styrene, 15 parts of isooctyl acrylate, 3 parts of acrylic acid and 3 parts of divinylbenzene, reacting at 80-90°C for 4 hours, keeping the temperature for 2 hours, cooling to 40°C and terminating the reaction to obtain an emulsion of polymer particles B, wherein the glass transition temperature of polymer particles B is 70°C and the particle size D of polymer particles B is 256 nm.
[0069] The emulsion of polymer particles A and the emulsion of polymer particles B are mixed at a mass ratio of polymer particles A to polymer particles B of 5:1 to obtain the separator binder composition of the present invention.
[0070] The present embodiment provides a method for preparing a diaphragm coating composition, comprising the following steps: mixing the above-mentioned diaphragm binder powder, auxiliary binder (SWA610 of Shenzhen Haodian Technology Co., Ltd., based on its solid mass), polysiloxane defoaming agent, and water in a mass ratio of 10:2:2:83, and obtaining a diaphragm coating composition after dispersion.
[0071] This embodiment provides a method for preparing a ceramic diaphragm, comprising the following steps: coating and rolling the above-mentioned diaphragm coating composition to obtain a ceramic diaphragm.
[0072] This embodiment provides a battery, which further includes a positive electrode sheet, a negative electrode sheet, a ceramic diaphragm, and an electrolyte.
[0073] Among them, the preparation of the positive electrode sheet: weigh each raw material according to the mass ratio (lithium cobalt oxide: carbon black: polyvinylidene fluoride = 90:5:5), add lithium cobalt oxide, carbon black, and polyvinylidene fluoride to the solvent, use a high-speed stirrer to fully mix, and prepare a uniform slurry. The prepared slurry is evenly coated on an aluminum foil current collector, and then dried in an oven to remove the solvent to form a uniform positive electrode sheet.
[0074] Preparation of negative electrode sheet: Weigh each raw material according to the mass ratio (graphite: carbon black: sodium carboxymethyl cellulose = 90:5:5), add graphite, carbon black and sodium carboxymethyl cellulose to the solvent, use a high-speed stirrer to fully mix, and prepare a uniform slurry. The prepared slurry is evenly coated on the copper foil current collector, and then dried in an oven to remove the solvent to form a uniform negative electrode sheet.
[0075] Preparation of electrolyte: Weigh the raw materials according to the mass ratio (lithium hexafluorophosphate:ethylene carbonate = 1:10), dissolve lithium hexafluorophosphate in ethylene carbonate, stir evenly, and prepare the electrolyte.
[0076] Battery assembly: prepare the positive electrode, negative electrode, ceramic diaphragm and electrolyte, stack the positive electrode, ceramic diaphragm and negative electrode in sequence, press at 4-5MPa for 60s at room temperature to form a battery core. Make sure that there is a ceramic diaphragm between the positive and negative electrodes to prevent short circuits. Place the battery core in the battery case, inject electrolyte, seal the battery case to ensure sealing, and age the assembled battery, usually leaving it at room temperature for 24 hours.
[0077] Example 2
[0078] Compared with Example 1, the raw materials for preparing polymer particles A include: 13 parts of acrylonitrile, 13 parts of styrene, 54 parts of butyl acrylate, 28 parts of isooctyl acrylate, and 3 parts of methacrylic acid; the glass transition temperature Tg thereof is tested to be -30°, and the average particle size D50 is 763 nm;
[0079] The raw materials for preparing polymer particles B include: 96 parts of styrene, 4 parts of isooctyl acrylate, 3 parts of acrylic acid, and 3 parts of divinylbenzene; the glass transition temperature Tg thereof is tested to be 90°, and the average particle size D50 is 231 nm;
[0080] The mass ratio of polymer particles A:polymer particles B is 7:3, and the remaining steps are the same as in Example 1.
[0081] Example 3
[0082] Compared with Example 2, the stirring speed during the preparation of polymer particles A and polymer particles B was adjusted; the glass transition temperature Tg of the prepared polymer particles A was tested to be -30°, and the average particle size D50 was 1408 nm; the glass transition temperature Tg of the polymer particles B was 90°, and the average particle size D50 was 291 nm; the remaining steps were the same as in Example 2.
[0083] Example 4
[0084] Compared with Example 2, the stirring speed during the preparation of polymer particles A and polymer particles B was adjusted; the glass transition temperature Tg of the prepared polymer particles A was tested to be -30°, and the average particle size D50 was 516 nm; the glass transition temperature Tg of the polymer particles B was 90°, and the average particle size D50 was 297 nm; the remaining steps were the same as in Example 2.
[0085] Example 5
[0086] Compared with Example 2, the stirring speed during the preparation of polymer particles A and polymer particles B was adjusted; the glass transition temperature Tg of the prepared polymer particles A was tested to be -30°, and the average particle size D50 was 656 nm; the glass transition temperature Tg of the polymer particles B was 90°, and the average particle size D50 was 128 nm; the remaining steps were the same as in Example 2.
[0087] Example 6
[0088] Compared with Example 1, the raw materials for preparing polymer particles A include: 5 parts of acrylonitrile, 25 parts of styrene, 30 parts of butyl acrylate, 50 parts of isooctyl acrylate, 2 parts of hydroxyethyl acrylate, and 1 part of methacrylic acid; the glass transition temperature Tg thereof is tested to be -30°, and the average particle size D50 is 752 nm;
[0089] The raw materials for preparing polymer particles B include: 96 parts of styrene, 4 parts of isooctyl acrylate, 3 parts of acrylic acid, and 3 parts of divinylbenzene; the glass transition temperature Tg thereof is tested to be 90°, and the average particle size D50 is 226 nm;
[0090] The mass ratio of polymer particles A:polymer particles B is 9:5, and the remaining steps are the same as in Example 1.
[0091] Example 7
[0092] Compared with Example 6, the mass ratio of polymer particles A:polymer particles B is 12:1, and the remaining steps are the same as Example 6.
[0093] Example 8
[0094] Compared with Example 6, the mass ratio of polymer particles A:polymer particles B is 3:5, and the remaining steps are the same as Example 6.
[0095] Example 9
[0096] Compared with Example 1, the raw materials for preparing polymer particles A include: 3 parts of styrene, 5 parts of butyl acrylate, 95 parts of isooctyl acrylate, and 2 parts of methacrylic acid; the glass transition temperature Tg thereof is tested to be -60°, and the average particle size D50 is 803 nm;
[0097] The raw materials for preparing polymer particles B include: 90 parts of styrene, 10 parts of isobornyl methacrylate, 5 parts of acrylic acid, and 5 parts of ethylene glycol dimethacrylate; the glass transition temperature Tg thereof is tested to be 120°, and the average particle size D50 is 263 nm;
[0098] The mass ratio of polymer particles A:polymer particles B is 7:3, and the remaining steps are the same as in Example 1.
[0099] Example 10
[0100] Compared with Example 1, the raw materials for preparing polymer particles A include: 3 parts of styrene, 5 parts of butyl acrylate, 95 parts of isooctyl acrylate, and 2 parts of methacrylic acid; the glass transition temperature Tg thereof is tested to be -30°, and the average particle size D50 is 957 nm;
[0101] The raw materials for preparing polymer particles B include: 96 parts of styrene, 4 parts of isooctyl acrylate, 3 parts of acrylic acid, and 3 parts of ethylene glycol dimethacrylate; the glass transition temperature Tg thereof is tested to be 90°, and the average particle size D50 is 285 nm;
[0102] The mass ratio of polymer particles A:polymer particles B is 7:3, and the remaining steps are the same as in Example 1.
[0103] Comparative Example 1
[0104] Compared with Example 1, the raw materials for preparing polymer particles A include: 13 parts of acrylonitrile, 45 parts of styrene, 30 parts of butyl acrylate, 22 parts of isooctyl acrylate, and 3 parts of methacrylic acid; the glass transition temperature Tg thereof is tested to be 5°, and the average particle size D50 is 533 nm;
[0105] The raw materials for preparing polymer particles B include: 85 parts of styrene, 15 parts of isooctyl acrylate, 3 parts of acrylic acid, and 2 parts of divinylbenzene; the glass transition temperature Tg thereof is tested to be 70°, and the average particle size D50 is 256 nm;
[0106] The mass ratio of polymer particles A:polymer particles B is 5:1, and the remaining steps are the same as in Example 1.
[0107] Comparative Example 2
[0108] Compared with Example 1, the raw materials for preparing polymer particles A include: 38 parts of styrene, 50 parts of butyl acrylate, 20 parts of isooctyl acrylate, and 3 parts of methacrylic acid; the glass transition temperature Tg thereof is tested to be -15°, and the average particle size D50 is 551 nm;
[0109] The raw materials for preparing polymer particles B include: 75 parts of styrene, 25 parts of isooctyl acrylate, 3 parts of acrylic acid, and 2 parts of divinylbenzene; the glass transition temperature Tg thereof is tested to be 30°, and the average particle size D50 is 264 nm;
[0110] The mass ratio of polymer particles A:polymer particles B is 5:1, and the remaining steps are the same as in Example 1.
[0111] Comparative Example 3
[0112] Compared with Example 1, the raw materials for preparing polymer particles A include: 38 parts of styrene, 50 parts of butyl acrylate, 20 parts of isooctyl acrylate, and 3 parts of methacrylic acid; the stirring speed is changed to prepare polymer particles A, and the glass transition temperature Tg thereof is tested to be -15°, and the average particle size D50 is 353 nm;
[0113] The polymer particles B of Comparative Example 1 have a glass transition temperature Tg of 70° and an average particle size D50 of 256 nm;
[0114] The mass ratio of polymer particles A:polymer particles B is 5:1, and the remaining steps are the same as in Example 1.
[0115] Comparative Example 4
[0116] Compared with Example 1, the polymer particles A of Comparative Example 1 have a glass transition temperature Tg of -15° and an average particle size D50 of 551 nm;
[0117] The raw materials for preparing polymer particles B include: 85 parts of styrene, 15 parts of isooctyl acrylate, 3 parts of acrylic acid, and 2 parts of divinylbenzene; the stirring speed is changed to prepare polymer particles B, and the glass transition temperature Tg thereof is tested to be 70°, and the average particle size D50 is 486 nm;
[0118] The mass ratio of polymer particles A:polymer particles B is 5:1, and the remaining steps are the same as in Example 1.
[0119] Comparative Example 5
[0120] Compared with Example 1, PVDF is used to replace the diaphragm adhesive composition provided by the present invention, and the remaining steps are the same as Example 1.
[0121] The diaphragms prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were rolled up, and it was observed whether sticking occurred.
[0122] The air permeability of Examples 1 to 10 and Comparative Examples 1 to 5 was tested using a Gurley air permeability meter. The test results are shown in Table 1.
[0123] The bonding strength of Examples 1 to 10 and Comparative Examples 1 to 5 was tested, and the test results are shown in Table 1;
[0124] An electronic tensile testing machine was used to test the peeling force and interface peeling strength of the electrode and diaphragm coating in accordance with the national standard GB / T 2792-2014 "Test method for peel strength of adhesive tape".
[0125] Table 1
[0126]
[0127] It can be seen from the results in Table 1 that the diaphragm binder powder prepared from the diaphragm binder composition provided by the present invention is applied to the coating on the surface of the diaphragm, and the obtained diaphragm has good air permeability, and there is no sticking phenomenon of the diaphragm during winding. It has good adhesion and stability to both the positive electrode sheet and the negative electrode sheet system, inhibits the deformation generated during the battery cell cycle, and prolongs the service life of the battery cell.
[0128] By comparing the test results of Example 5 and Example 2, it can be seen that when the particle size ratio of polymer particles A to polymer particles B is too large, it will cause slight sticking phenomenon when the diaphragm is rolled up.
[0129] By comparing the test results of Example 7 and Example 2, it can be seen that when the amount of polymer particles A is too large relative to the amount of polymer particles B, it will cause the diaphragm to stick when it is rolled up, and the air permeability value-added of the diaphragm will increase. It is speculated that the reason is that on the one hand, there are too few polymer particles B and they cannot be effectively distributed on the surface of polymer particles A, and the effect of inhibiting the sticking phenomenon is not obvious. On the other hand, there are too many polymer particles A, which will cause film formation, thereby increasing the air permeability value-added.
[0130] By comparing the test results of Example 1 and Comparative Example 1, it can be seen that the glass transition temperature of polymer particles A is too high and the peel strength is significantly reduced.
[0131] By comparing the test results of Example 1 and Comparative Example 2, it can be seen that the glass transition temperature of the polymer particles B is too low, which will cause the membrane to be rolled up and sticky, and the air permeability of the membrane will increase.
[0132] By comparing the test results of Example 1 with Comparative Examples 3 and 4, it can be seen that if the particle size of polymer particles A is too small or the particle size of polymer particles B is too large, the peel strength will be insufficient.
[0133] By comparing the test results of Example 1 and Comparative Example 5, it can be seen that, compared with the traditional PVDF adhesive, the diaphragm adhesive provided by the present invention can effectively improve the phenomenon of diaphragm sticking during rolling, and the air permeability of the diaphragm is significantly better.
[0134] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A diaphragm adhesive composition, characterized in that: The invention comprises polymer particles A and polymer particles B, wherein the glass transition temperature Tg of the polymer particles A is -70 to -10°C, and the average particle size D50 of the polymer particles A is 500 to 1500 nm; the glass transition temperature Tg of the polymer particles B is 60 to 150°C, and the average particle size D50 of the polymer particles B is 100 to 300 nm; The mass ratio of the polymer particles A to the polymer particles B is (5-9): (1-5); The average particle size ratio of the polymer particles A to the polymer particles B is (5-15):3; The polymer particles A include vinyl structural units, acrylic ester structural units and functional structural units; The vinyl structural unit is selected from one or more of styrene, acrylonitrile, methylstyrene, and ethylstyrene; The acrylic acid ester structural unit is selected from one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, isooctyl acrylate, n-pentyl methacrylate, n-hexyl methacrylate, n-octyl methacrylate, isooctyl methacrylate, and lauryl methacrylate; The functional structural unit is selected from one or more of acrylic acid, methacrylic acid, vinyl acrylic acid, β-acryloxypropionic acid, hydroxy acrylic acid, maleic acid, itaconic acid, monobutyl itaconate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate; The polymer particles B include a main structural unit and a cross-linking structural unit; The main structural unit is selected from a plurality of the group consisting of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, isooctyl acrylate, styrene, methyl styrene, methyl methacrylate, isobornyl acrylate, isobornyl methacrylate, acrylic acid, methacrylic acid, and itaconic acid; The cross-linked structural unit is selected from one or more of diol diacrylate, bisphenol A diacrylate, azacycloalkane diacrylate, divinyl aromatic hydrocarbon, diol dimethacrylate, bisphenol A dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and pentaerythritol tetraacrylate; In the polymer particles A, the mass ratio of the vinyl structural unit, the acrylate structural unit and the functional structural unit is (0-35): (60-95): (1-5), and the vinyl structural unit is not 0; In the polymer particles B, the mass ratio of the main structural unit to the cross-linking structural unit is 100:(2-10).
2. The diaphragm adhesive composition according to claim 1, characterized in that Polymer particles B are distributed on the surface of the polymer particles A, and the surface of the polymer particles A is at least partially covered by the polymer particles B.
3. A diaphragm binder powder, characterized in that: The diaphragm binder powder is a secondary particle formed by the diaphragm binder composition as described in any one of claims 1-2, and the secondary particles include polymer particles A and polymer particles B distributed on the surface of polymer particles A, and the surface of polymer particles A is at least partially covered by polymer particles B.
4. A diaphragm, characterized in that: The diaphragm includes the diaphragm binder powder according to claim 3.
5. A battery, characterized in that: The battery comprises the separator according to claim 4.
Citation Information
Patent Citations
Lithium ion battery composite isolation membranes
CN102810655A
Multilayer composite lithium ion battery diaphragm and preparation method thereof
CN115172986A